Experience with advanced welding techniques (RMD & P-GMAW) with seamless metal cored wire for Oil & Gas pipeline industries. Issue 1 (August 2021) - Das, Subhash; Vora, Jaykumar; Patel, Vivek; Bogum, Surender
Abstract: Regulated Metal Deposition (RMD™) process is a variant of Gas metal arc welding process (GMAW), which was developed with the aim to effectively control the metal transfer in the short-circuiting mode. The process is fundamentally a modified short-circuit GMAW process wherein a uniform droplet deposition, making it easier for the welder to control the puddle and hence achieve an enhanced quality of welded joints. In the present study, RMD technique has been established for API grade pipe (API 5L PSL2 X70 grade) particularly for depositing the root pass on 24" OD and 10.3 mm thick pipe. In addition to this, the RMD technique is tried for the first time with seamless metal cored wires (Megafill 240 M) in order to enhance the deposition rates in Indian Oil & Gas pipeline industry. The joint fill up is further attempted with pulsed GMAW technique using metal cored wires and further analysed. The weldments were tested by mechanical characterization. Mechanical characterization such as tensile properties, impact properties, bend test as well as all weld tensile properties of the weld joint were evaluated and found to be acceptable. A techno-commercial evaluation of the technique was carried out vis-à-vis conventional welding techniques such as SMAW process for root passes and Fill & Cap. It was found the proposed technique was cost effective as well as reliable. One of the inherent benefits of the RMD and Pulse GMAW technique is the reduction in the overall heat input of the welded joint imparting superior mechanical properties. The use of metal cored wires also established the proposed technique as a potential technique for heavy thick weldments by enhancing the overall productivity.